Feminist theology and a generous orthodoxy - Greene-McCreight, Kathryn (Scottish journal of theology, 2004)
How do a generous orthodoxy and contemporary feminist theology relate and work together, if at all? Can feminist theology have something to say to a generous orthodoxy other than blatant critique? Orthodoxy is seen as that view expressed in the rule of faith as early as Irenaeus and Tertullian, and is a constellation of beliefs which link Creator with Christ, OT with NT, and which employs the interpretation of scripture ‘according to itself’. A definition of generous orthodoxy means a Christ-like submission to the Other, and reasoning about God, three in one, through meditation on the scriptures and tradition of the church such that one's soul is turned to praise. A simple definition of feminist theology is ‘the radical notion that women are people too’ (so Elisabeth Schüssler Fiorenza, Sharing Her Word: Feminist Biblical Interpretation in Context, 1998). Can these two ways of envisioning the theological task work together, and if so, to what extent? With key doctrines and concepts of feminist theology such as patriarchy, women's experience, feminist consciousness, one questions the fit between orthodoxy and feminist theology, but of course this is purposefully so on the basis of feminist principles and dogmas. We will examine and compare the construction of sin, Christology and the trinity in feminist theologies and generously orthodox theologies to clarify the discussion.